Thrombolysis of bowel obstruction? A thought-provoking presentation of a common surgical pathology. Issue 3 (28th March 2023) - Raythatha, Jineel H; Tucker, Bradley; Lester, Geoffrey; Eather, Samuel; Lambert, Ben
Abstract: We present a unique case of bowel obstruction with a hiatus hernia causing atypical chest pain with dynamic ST-segment elevation in a regional Australian emergency department. The ST elevation only resolved after nasogastric decompression of the bowel obstruction. Early thrombolysis of presumed myocardial infarction led to upper gastrointestinal tract bleeding that could have been avoided with timely diagnosis. An extensive review of literature, in addition to our case report, suggests bowel obstruction is a differential diagnosis for patients who have inferior pattern ST elevation but normal troponin presenting with atypical chest pain, nausea, vomiting and previous abdominal surgery.